2013
DOI: 10.3389/fpubh.2013.00052
|View full text |Cite
|
Sign up to set email alerts
|

Recycling Metchnikoff: Probiotics, the Intestinal Microbiome and the Quest for Long Life

Abstract: Over a century ago, Elie Metchnikoff theorized that health could be enhanced and senility delayed by manipulating the intestinal microbiome with host-friendly bacteria found in yogurt. His theory flourished for a time, then drifted to the fringe of medical practice before re-emerging in the mid-1990s as a concept worthy of mainstream medical attention. Metchnikoff also predicted the existence of bacterial translocation and anticipated theories linking chronic inflammation with the pathogenesis of atheroscleros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
122
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(143 citation statements)
references
References 5 publications
(5 reference statements)
1
122
0
4
Order By: Relevance
“…The majority of the probiotics available at present include lactic acid bacteria (20), in addition to the genera Lactobacillus, Bifidobacterium and Enterococcus (21). Studies in animal models and humans have demonstrated that the consumption of probiotics is effective in various medical conditions, can delay senility (22), and improve acute infectious diarrhea (23,24), antibiotic-associated diarrhea (21,25), constipation (26)(27)(28), ulcerative colitis (29,30) and Crohn's disease (31,32). However, the majority of these previous studies focused on the interaction between probiotics and the mammalian host.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the probiotics available at present include lactic acid bacteria (20), in addition to the genera Lactobacillus, Bifidobacterium and Enterococcus (21). Studies in animal models and humans have demonstrated that the consumption of probiotics is effective in various medical conditions, can delay senility (22), and improve acute infectious diarrhea (23,24), antibiotic-associated diarrhea (21,25), constipation (26)(27)(28), ulcerative colitis (29,30) and Crohn's disease (31,32). However, the majority of these previous studies focused on the interaction between probiotics and the mammalian host.…”
Section: Introductionmentioning
confidence: 99%
“…İntestinal florada patojenik mikroorganizmaların kolonizasyonunu ve çoğalmasını önleyerek konağın savunmasındaki olumlu etkilerinin yanı sıra birçok metabolik olayda görev alırlar. Ayrıca immün sistemde önemli değişikliklerin olduğu doğumdan sonraki dönemde lokal ve sistemik immün yanıtın şekillenmesinde önemli roller oynamaktadırlar (13)(14)(15).…”
Section: Bağırsak Florası Ve öNemiunclassified
“…In 1907 Élie Metchnikoff; a Russian zoologist best known for his pioneering research in immunology; put the auto intoxication theory and suggested that changing the harmful intestinal flora with beneficial one can prevent aging [1].…”
Section: Introductionmentioning
confidence: 99%
“…First commercially sold diary-based probiotic (Yakult) in 1935 was a mixture of fermented skimmed milk and Lactobacillus casei Shirota, first launched in japan [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation